Kinship Systems and the Internalization of Islamic Values among the Madurese Community in Tanean Lanjheng - Fanani, Zainal; Ilmi, Vika Wafa; Br Siregar, Wahidah Zein; Maskuri, Arfan (An-Nida', 2025)
The kinship system within Tanean Lanjheng plays a pivotal role in the transmission and internalization of Islamic values in the daily lives of the Madurese community. This process of internalization occurs within a traditional social space that not only reflects a physical settlement pattern but also embodies cultural symbols and practices deeply intertwined with religious teachings. This study seeks to analyze the kinship system present in Tanean Lanjheng settlements and to examine the mechanisms through which Islamic values are perpetuated across generations. Employing a qualitative case study approach, the research was conducted in Lieson Hamlet, Sumenep, utilizing participatory observation and in-depth interviews with local community leaders. Data analysis was informed by Berger and Luckmann’s theory of social construction, Émile Durkheim’s concept of social facts, and Clifford Geertz’s notion of the cultural broker. The findings indicate that Tanean Lanjheng operates as a matrilineal social system that facilitates the collective transmission of Islamic values through processes of exemplification (uswah) and habituation (ta’dib), with the ghuru (teacher/cleric) serving as the principal agent. The internalization of values transpires not only through ritual practices but also via quotidian interactions and kinship solidarity. Nonetheless, the study identifies significant challenges, including the erosion of central family figures, social fragmentation resulting from youth mobility, and stratified patterns of value internalization linked to families’ socio-religious status. These findings underscore the significance of Tanean Lanjheng as a contextually grounded model of Islamic values education that retains its relevance amid modernization. Abstrak: Sistem kekerabatan di Tanean Lanjheng memiliki peran strategis dalam mewariskan serta menginternalisasi nilai-nilai keislaman dalam kehidupan masyarakat Madura. Internalisasi ini berlangsung melalui ruang sosial tradisional yang bukan hanya merepresentasikan tata ruang fisik, tetapi juga mengandung simbol dan praktik budaya yang terintegrasi dengan ajaran agama. Penelitian ini bertujuan menganalisis sistem kekerabatan dalam pemukiman Tanean Lanjheng serta mengkaji bagaimana proses internalisasi nilai keislaman dijalankan secara turun-temurun. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus yang dilakukan di Dusun Lieson, Sumenep, melalui observasi partisipatif dan wawancara mendalam dengan tokoh lokal. Analisis data mengacu pada teori konstruksi sosial Berger & Luckmann, konsep fakta sosial Émile Durkheim, dan gagasan cultural broker Clifford Geertz. Hasil penelitian menunjukkan bahwa Tanean Lanjheng berfungsi sebagai sistem sosial matrilineal yang memfasilitasi transmisi nilai Islam secara kolektif melalui mekanisme keteladanan (uswah) dan pembiasaan (ta’dib), dengan figur ghuru (guru/kiai) sebagai agen utama. Internalisasi nilai berlangsung tidak hanya dalam ranah ritual, tetapi juga melalui praktik keseharian dan solidaritas kekerabatan. Namun, penelitian juga menemukan tantangan serius, antara lain hilangnya figur sentral keluarga, fragmentasi sosial akibat mobilitas generasi muda, serta adanya stratifikasi pola internalisasi berdasarkan status sosial-keagamaan keluarga. Temuan ini menegaskan bahwa keberadaan Tanean Lanjheng penting sebagai model pendidikan nilai Islam yang kontekstual, berakar pada budaya lokal, sekaligus adaptif menghadapi arus modernisasi.